(untitled) (Psychology Travelogs, 2025)
The article examines trauma-informed supervision as a crucial component of professional support for psychologists providing assistance to internally displaced persons (IDPs) due to the war in Ukraine. It highlights the relevance of supervision in the context of increased risks of professional burnout, secondary traumatization, and compassion fatigue among specialists. Based on the analysis of literature sources and empirical data, key principles of trauma-informed supervision are clarified, including ensuring safety, trust, peer-to-peer support, and consideration of cultural, historical, and gender aspects. The study employs a case analysis method, which allows for a detailed exploration of the mechanisms of supervision in the context of psychological support for IDPs. A specific case of supervising a clinical psychologist working with volunteers who have themselves experienced forced displacement is analyzed. The emotional challenges faced by the supervisee are identified, including feelings of guilt, frustration, and confusion due to the emotional reactions of the group. Emphasis is placed on the importance of validating the supervisee’s emotions, providing psychoeducation on the dynamics of traumatic experiences, and creating a safe space for reflection. The results of the analysis confirm the significance of trauma-informed supervision in supporting psychologists working with IDPs, as it not only enhances the quality of psychological assistance but also promotes the professional and emotional well-being of specialists. The article also presents practical recommendations for supervisors on preventing secondary traumatic stress and burnout among professionals working in trauma-related contexts. The recommendations outline the key requirements for supervisors, including deep knowledge and a humanistic approach.